Chemical Kinetic Study of Nitrogen Oxides Formation Trends in Biodiesel Combustion - Junfeng Yang; Valeri I. Golovitchev; Pau Redón Lurbe; J. Javier López Sánchez (International Journal of Chemical Engineering)
The use of biodiesel in conventional diesel engines results in increased NOx emissions; this presents a barrier to the widespread use of biodiesel. The origins of this phenomenon were investigated using the chemical kinetics simulation tool: CHEMKIN-2 and the CFD KIVA3V code, which was modified to account for the physical properties of biodiesel and to incorporate semidetailed mechanisms for its combustion and the formation of emissions. Parametric ϕ-T maps and 3D engine simulations were used to assess the impact of using oxygen-containing fuels on the rate of NO formation. It was found that using oxygen-containing fuels allows more O2 molecules to present in the engine cylinder during the combustion of biodiesel, and this may be the cause of the observed increase in NO emissions.